2021
DOI: 10.1093/jpe/rtab003
|View full text |Cite
|
Sign up to set email alerts
|

Variation and potential influence factors of foliar pH in land-water ecozones of three small plateau lakes

Abstract: Aims Foliar pH of terrestrial plants, a trait tightly associated with plant physiology and nutrient utilization, varies with plant functional types (PFT) and environmental changes. However, it is yet unclear about the variation in foliar pH of aquatic plants, and the difference between aquatic and terrestrial plants. Methods Foliar pH, leaf carbon, nitrogen content of plants along the lakeshore zones and the environmental con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Therefore, the internalization process likely involves the dissolution of MnNPs into Mn ions, which was enhanced by the high humidity in the growth chamber (70%) or due to the low leaf surface pH. Although foliar pH can be affected by plant species and soil type, reported levels are commonly between 5 and 6. , Therefore, time-dependent structural changes in the aggregates on the leaf surfaces were observed. Interestingly, Ye et al reported that foliar exposure to MnNPs (60–250 mg/L) increased the biosynthesis of long-chain n -alkanes in C. annuum L. leaf wax .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the internalization process likely involves the dissolution of MnNPs into Mn ions, which was enhanced by the high humidity in the growth chamber (70%) or due to the low leaf surface pH. Although foliar pH can be affected by plant species and soil type, reported levels are commonly between 5 and 6. , Therefore, time-dependent structural changes in the aggregates on the leaf surfaces were observed. Interestingly, Ye et al reported that foliar exposure to MnNPs (60–250 mg/L) increased the biosynthesis of long-chain n -alkanes in C. annuum L. leaf wax .…”
Section: Resultsmentioning
confidence: 99%
“…Although foliar pH can be affected by plant species and soil type, reported levels are commonly between 5 and 6. 24,25 Therefore, timedependent structural changes in the aggregates on the leaf surfaces were observed. Interestingly, Ye et al reported that foliar exposure to MnNPs (60−250 mg/L) increased the biosynthesis of long-chain n-alkanes in C. annuum L. leaf wax.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Planktonic algae and aquatic plants can absorb and utilize water DIC through photosynthesis [ 54 ], so lower levels of planktonic algae lead to weaker photosynthesis in the water column, which, in turn, reduces the amount of DIC absorbed and used in the water [ 55 ]. These processes inevitably cause changes in the pH of the water [ 56 ], which affect the growth activities of microorganisms and algae [ 57 , 58 ], which affect DOC release and TN decomposition. Dead cells of planktonic algae release high-molecular-weight DOC, while living cells release low-molecular-weight DOC [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plant pH, especially leaf pH, is a valuable plant functional trait, which is believed to be a species-specific trait with large-scale spatio-temporal patterns [4][5][6][7]. Leaf pH can not only regulate the nutrient cycling and biological relationships [5,8,9], but also indicate the air pollution [10], reveal plant responses to the environment and jointly affects plant survival strategies with other plant functional traits [6,[11][12][13]. Thus, focusing our attention on leaf pH is of great significance to both plant physiology and ecology.…”
Section: Introductionmentioning
confidence: 99%